Temporal epidemiological profile of oral potentially malignant disorders in southern Brazil - Natália Souza dos SANTOS; Amanda Zimmer RODRIGUES; Camila Alves FERRI; Taiane Berguemaier de LIMA; Natalia Koerich LAUREANO; Pantelis Varvaki RADOS; Vinícius Coelho CARRARD; Laura de Campos HILDEBRAND; Fernanda VISIOLI (Brazilian Oral Research)
Abstract The study aimed to investigate oral potentially malignant disorders (OPMDs) diagnosed in an Oral Pathology service in southern Brazil over a span of 56 years and to assess the factors influencing their severity and outcomes. A retrospective analysis of histopathological records from 1965 to 2021 was performed. Lesions diagnosed as leukoplakia, erythroplakia, leukoerythroplakia, or actinic cheilitis were included. Data on age, sex, race, tobacco smoking, alcohol drinking, clinical characteristics, biopsy type, and histopathological diagnosis were collected. Among 32.698 histopathological reports, 2.10% were classified as OPMD. The study included 689 specimens from 602 patients, with a predominance of cases affecting men aged over 51 years, particularly in anatomical sites considered of low risk. White lesions, with leukoplakia as the most common clinical diagnosis were observed. Over time, there was an increase in the incidence of OPMDs among females and in high-risk anatomical sites. The mean follow-up period was 30.28 ± 29.86 months, during which 9.6% of cases exhibited malignant transformation. Lesions diagnosed as leukoerythroplakia and those presenting epithelial dysplasia exhibited a higher risk of malignant transformation, particularly when located in high-risk sites. This underscores the importance of identifying clinical and microscopic features, as well as lesion’s anatomical location, as crucial factors in determining the risk of malignant transformation. These findings provide valuable insights for clinicians managing OPMDs and contribute to the improvement of oral cancer prevention.